Microcrystal metal ceramic plate and production process thereof
By using raw materials such as kaolin, quartz sand and combining modified fibers and clay, the microcrystalline metal cermet plates made solve the problems of poor impact resistance and easy corrosion in traditional materials, achieving high strength, corrosion resistance and environmental protection architectural decorative materials.
Patent Information
- Application Number
- CN202411460568.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-18
- Publication Date
- 2025-02-18
AI Technical Summary
The existing building decoration materials have poor impact resistance, easy corrosion, large weight, complex production process, and high cost in terms of performance, which is difficult to meet the market's comprehensive needs for aesthetics, durability, environmental protection and versatility.
Use microcrystalline metal cermet plates composed of raw materials such as kaolin, quartz sand, feldspar powder, modified fibers, modified clay, polyvinyl alcohol and polyammonium methacrylate, and granulation through spray drying, dry press molding and high-temperature drying. Made in process steps.
It significantly improves the impact resistance and corrosion resistance of ceramic plates, enhances its overall mechanical properties, including flexural strength and compressive strength, while reducing production costs and simplifying the process flow.
Smart Images

Figure BDA0005091749690000111 
Figure BDA0005091749690000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of microcrystalline metal ceramic panels, and in particular to a microcrystalline metal ceramic panel and a production process thereof. Background Art
[0002] With the rapid development of the modern construction industry, the requirements for building decoration materials are increasing day by day. Traditional materials such as tiles and stones can no longer meet the market's comprehensive needs for aesthetics, durability, environmental protection and versatility. In this context, microcrystalline metal ceramic panels have emerged as a new type of building decoration material. Its unique physical properties and wide application prospects have attracted widespread attention in the industry.
[0003] Microcrystalline metal ceramic panels are a new type of composite material made from natural minerals, metal oxides and kaolin through special processing. Its core technology is to use high-temperature sintering to make the minerals and metal oxides in the raw materials crystallize, forming a microcrystalline structure with excellent properties such as high strength, high hardness, moisture resistance, heat resistance, anti-fouling and easy cleaning. This material not only inherits the advantages of traditional ceramic materials, but also incorporates the characteristics of metal materials, thereby significantly improving its comprehensive performance.
[0004] Although there are many similar building decoration materials on the market, they still have many deficiencies in performance. For example, although traditional ceramic materials are beautiful and durable, they have poor impact resistance and are easy to break; while metal materials have disadvantages such as easy corrosion and heavy weight. In addition, some new composite materials are relatively complex in production process and have high costs, making them difficult to promote and apply on a large scale. Based on this, the present invention proposes a microcrystalline metal ceramic panel and its production process. Summary of the invention
[0005] The purpose of the present invention is to provide a microcrystalline metal ceramic plate and a production process thereof, which improves the impact resistance and the corrosion resistance of the ceramic plate.
[0006] In a first aspect, the present invention provides a microcrystalline metal ceramic plate, which is composed of the following raw materials in parts by weight: 10-15 parts of kaolin, 10-20 parts of quartz sand, 10-15 parts of feldspar powder, 1-3 parts of silane coupling agent modified fiber, 12-14 parts of modified clay, 4-5 parts of polyvinyl alcohol, 0.4-0.6 parts of ammonium polymethacrylate, and 35-45 parts of water.
[0007] Furthermore, the preparation method of the modified fiber includes: adding titanium dioxide fiber and aluminum oxide fiber to deionized water for ultrasonic cleaning for 1 hour, then immersing them in a sodium hydroxide solution at a temperature of 50-60°C to react for 30-40 minutes, washing with water until neutral to obtain a pretreated mixed fiber, mixing the pretreated mixed fiber, a silane coupling agent and ethanol, and reacting them at a temperature of 65-75°C for 40-50 minutes. After the reaction is completed, filtering and drying are performed.
[0008] Furthermore, the length of the titanium dioxide fiber is 100-120 nm, and the length of the aluminum oxide fiber is 20-30 nm.
[0009] Furthermore, the sodium hydroxide solution is a sodium hydroxide aqueous solution with a mass concentration of 3-4%.
[0010] Furthermore, the weight ratio of the titanium dioxide fiber, the aluminum oxide fiber, the silane coupling agent and the ethanol is (8-10): (5-10): (1.5-2.5): (50-60).
[0011] Furthermore, the silane coupling agent includes at least one of KH550, KH560 and KH570.
[0012] Furthermore, the preparation method of the modified clay comprises: firstly calcining the clay at a temperature of 800-860° C. for 2-2.4 hours, adding stearic acid monoglyceride after calcination, and mixing and stirring at a temperature of 65-75° C. for 60-80 minutes to obtain the modified clay.
[0013] Furthermore, the weight ratio of the clay to stearic acid monoglyceride is (15-20):(0.1-0.3).
[0014] In a second aspect, the present invention provides a production process for a microcrystalline metal ceramic plate, the steps comprising: weighing raw materials and mixing them to form a mixture, spray drying and granulating to obtain 80-100 mesh green body powder particles, dry pressing after drying, and drying at a temperature of 160-180°C.
[0015] Furthermore, the moisture content of the green body after drying is 2-3%.
[0016] The beneficial effects of the present invention are:
[0017] The present invention uses kaolin, quartz sand, feldspar powder and other inorganic mineral raw materials as the basis of ceramic materials, which provide the main structure and strength of the ceramic plate. Kaolin has good plasticity and bonding properties, and quartz sand and feldspar powder increase the hardness and wear resistance of the ceramic plate.
[0018] The present invention modifies titanium dioxide fiber and alumina fiber by using a silane coupling agent. Through the modification of the silane coupling agent, the surface of the titanium dioxide fiber and the alumina fiber is endowed with functional groups that can form chemical bonds with the ceramic matrix. This chemical bonding significantly enhances the bonding force between the fiber and the matrix, so that the fiber can better disperse and absorb energy when impacted by external forces, thereby improving the impact resistance of the ceramic plate; when the ceramic plate is impacted, the modified fiber can connect the broken ceramic particles like a bridge to prevent the further expansion of the cracks. This bridging effect not only improves the toughness of the ceramic plate, but also extends its service life; in addition, the fiber also has a certain reinforcement effect. Since the titanium dioxide fiber and the alumina fiber themselves have high strength and modulus, their addition can significantly improve the overall mechanical properties of the ceramic plate, including bending strength and compressive strength.
[0019] In the present invention, the clay is subjected to high-temperature calcination and modification treatment with stearic acid monoglyceride, which not only removes some impurities, but also improves the compactness and corrosion resistance of the clay. After the clay is calcined at high temperature, the impurities and moisture inside it are removed, and the structure becomes more compact and stable. This compact structure helps to reduce the penetration and erosion of corrosive media on the ceramic plate. Stearic acid monoglyceride forms a protective film on the surface of the clay particles. This protective film can prevent corrosive media (such as water, acid, alkali, etc.) from direct contact with the clay particles, thereby improving the corrosion resistance of the ceramic plate. In addition, stearic acid monoglyceride may further reduce the water absorption of the ceramic plate through its hydrophobic properties, thereby reducing corrosion caused by water intrusion.
[0020] In the present invention, polyvinyl alcohol and ammonium polymethacrylate as organic additives play a bonding and dispersing role in the ceramic preparation process, which helps to improve the mixing uniformity of raw materials and the forming performance of the green body. DETAILED DESCRIPTION
[0021] The technical solution of the present invention is described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0022] Example 1
[0023] The present embodiment provides a microcrystalline metal ceramic plate, which is composed of the following raw materials in parts by weight: 12 parts of kaolin, 15 parts of quartz sand, 12 parts of feldspar powder, 2 parts of silane coupling agent modified fiber, 13 parts of modified clay, 4.5 parts of polyvinyl alcohol, 0.5 parts of ammonium polymethacrylate, and 40 parts of water.
[0024] The preparation method of the modified fiber comprises: adding titanium dioxide fiber and aluminum oxide fiber to deionized water for ultrasonic cleaning for 1 hour, then immersing in a sodium hydroxide aqueous solution with a temperature of 55° C. and a mass concentration of 3.5% to react for 35 minutes, washing with water until neutral to obtain a pretreated mixed fiber, mixing the pretreated mixed fiber, a silane coupling agent and ethanol, reacting at a temperature of 70° C. for 45 minutes, filtering after the reaction, and drying to obtain the modified fiber;
[0025] Among them, the length of the titanium dioxide fiber is 110nm, the length of the aluminum oxide fiber is 25nm; the weight ratio of the titanium dioxide fiber, the aluminum oxide fiber, the silane coupling agent and ethanol is 9:7:2:55; the silane coupling agent is KH550.
[0026] The preparation method of the modified clay comprises: firstly calcining the clay at a temperature of 830° C. for 2.2 hours, adding stearic acid monoglyceride after calcination, and mixing and stirring at a temperature of 70° C. for 70 minutes to obtain the modified clay; the weight ratio of the clay to stearic acid monoglyceride is 17:0.2.
[0027] This embodiment also provides a production process of a microcrystalline metal ceramic plate, comprising the following steps: weighing raw materials and mixing them to form a mixture, spray drying and granulating to obtain 90-mesh green body powder particles, drying and dry pressing, and drying at a temperature of 170° C. The moisture content of the green body after drying is 2.5%.
[0028] Example 2
[0029] The present embodiment provides a microcrystalline metal ceramic plate, which is composed of the following raw materials in parts by weight: 10 parts of kaolin, 10 parts of quartz sand, 10 parts of feldspar powder, 1 part of silane coupling agent modified fiber, 12 parts of modified clay, 4 parts of polyvinyl alcohol, 0.4 parts of ammonium polymethacrylate, and 35 parts of water.
[0030] The preparation method of the modified fiber comprises: adding titanium dioxide fiber and aluminum oxide fiber to deionized water for ultrasonic cleaning for 1 hour, then immersing in a sodium hydroxide aqueous solution with a temperature of 50° C. and a mass concentration of 3% to react for 30 minutes, washing with water until neutral to obtain a pretreated mixed fiber, mixing the pretreated mixed fiber, a silane coupling agent and ethanol, reacting at a temperature of 65° C. for 40 minutes, filtering after the reaction, and drying to obtain the modified fiber;
[0031] Among them, the length of the titanium dioxide fiber is 100nm, the length of the aluminum oxide fiber is 20nm; the weight ratio of the titanium dioxide fiber, the aluminum oxide fiber, the silane coupling agent and ethanol is 8:5:1.5:50; the silane coupling agent is KH550.
[0032] The preparation method of the modified clay comprises: firstly calcining the clay at a temperature of 800° C. for 2 hours, adding stearic acid monoglyceride after calcination, and mixing and stirring at a temperature of 65° C. for 60 minutes to obtain the modified clay; the weight ratio of the clay to stearic acid monoglyceride is 15:0.1.
[0033] This embodiment also provides a production process of a microcrystalline metal ceramic plate, comprising the following steps: weighing raw materials and mixing them to form a mixture, spray drying and granulating to obtain 80-mesh green body powder particles, drying and dry pressing, and drying at a temperature of 160° C. The moisture content of the green body after drying is 2%.
[0034] Example 3
[0035] The present embodiment provides a microcrystalline metal ceramic plate, which is composed of the following raw materials in parts by weight: 15 parts of kaolin, 20 parts of quartz sand, 15 parts of feldspar powder, 3 parts of silane coupling agent modified fiber, 14 parts of modified clay, 5 parts of polyvinyl alcohol, 0.6 parts of ammonium polymethacrylate, and 45 parts of water.
[0036] The preparation method of the modified fiber comprises: adding titanium dioxide fiber and aluminum oxide fiber to deionized water for ultrasonic cleaning for 1 hour, then immersing in a sodium hydroxide aqueous solution with a temperature of 60° C. and a mass concentration of 4% to react for 40 minutes, washing with water until neutral to obtain a pretreated mixed fiber, mixing the pretreated mixed fiber, a silane coupling agent and ethanol, reacting at a temperature of 75° C. for 50 minutes, filtering after the reaction, and drying to obtain the modified fiber;
[0037] Among them, the length of the titanium dioxide fiber is 120nm, the length of the aluminum oxide fiber is 30nm; the weight ratio of the titanium dioxide fiber, the aluminum oxide fiber, the silane coupling agent and ethanol is 10:10:2.5:60; the silane coupling agent is KH560.
[0038] The preparation method of the modified clay comprises: firstly calcining the clay at a temperature of 860° C. for 2.4 hours, adding stearic acid monoglyceride after calcination, and mixing and stirring at a temperature of 75° C. for 80 minutes to obtain the modified clay; the weight ratio of the clay to stearic acid monoglyceride is 20:0.3.
[0039] This embodiment also provides a production process of a microcrystalline metal ceramic plate, comprising the following steps: weighing raw materials and mixing them to form a mixture, spray drying and granulating to obtain 100-mesh green body powder particles, drying and dry pressing, and drying at a temperature of 180° C. The moisture content of the green body after drying is 3%.
[0040] Example 4
[0041] The present embodiment provides a microcrystalline metal ceramic plate, which is composed of the following raw materials in parts by weight: 10 parts of kaolin, 20 parts of quartz sand, 10 parts of feldspar powder, 3 parts of silane coupling agent modified fiber, 12 parts of modified clay, 5 parts of polyvinyl alcohol, 0.4 parts of ammonium polymethacrylate, and 45 parts of water.
[0042] The preparation method of the modified fiber comprises: adding titanium dioxide fiber and aluminum oxide fiber to deionized water for ultrasonic cleaning for 1 hour, then immersing in a sodium hydroxide aqueous solution with a temperature of 50° C. and a mass concentration of 4% to react for 30 minutes, washing with water until neutral to obtain a pretreated mixed fiber, mixing the pretreated mixed fiber, a silane coupling agent and ethanol, reacting at a temperature of 75° C. for 40 minutes, filtering after the reaction, and drying to obtain the modified fiber;
[0043] Among them, the length of the titanium dioxide fiber is 120nm, the length of the aluminum oxide fiber is 30nm; the weight ratio of the titanium dioxide fiber, the aluminum oxide fiber, the silane coupling agent and ethanol is 8:10:1.5:60; the silane coupling agent is KH570.
[0044] The preparation method of the modified clay comprises: firstly calcining the clay at a temperature of 800° C. for 2.4 hours, adding stearic acid monoglyceride after calcination, and mixing and stirring at a temperature of 65° C. for 80 minutes to obtain the modified clay; the weight ratio of the clay to stearic acid monoglyceride is 15:0.3.
[0045] This embodiment also provides a production process of a microcrystalline metal ceramic plate, comprising the following steps: weighing raw materials and mixing them to form a mixture, spray drying and granulating to obtain 80-mesh green body powder particles, drying and dry pressing, and drying at a temperature of 180° C. The moisture content of the green body after drying is 2%.
[0046] Comparative Example 1
[0047] The present comparative example provides a microcrystalline metal ceramic plate, which is composed of the following raw materials in parts by weight: 12 parts of kaolin, 15 parts of quartz sand, 12 parts of feldspar powder, 2 parts of silane coupling agent modified fiber, 13 parts of modified clay, 4.5 parts of polyvinyl alcohol, 0.5 parts of ammonium polymethacrylate, and 40 parts of water.
[0048] The preparation method of the modified fiber comprises: adding titanium dioxide fiber to deionized water for ultrasonic cleaning for 1 hour, then immersing in a sodium hydroxide aqueous solution with a temperature of 55° C. and a mass concentration of 3.5% for reaction for 35 minutes, washing with water until neutral to obtain pretreated fiber, mixing the pretreated fiber, a silane coupling agent and ethanol, reacting at a temperature of 70° C. for 45 minutes, filtering after the reaction, and drying to obtain the fiber;
[0049] The length of the titanium dioxide fiber is 110 nm, the weight ratio of the titanium dioxide fiber, the silane coupling agent and ethanol is 9:2:55; and the silane coupling agent is KH550.
[0050] The preparation method of the modified clay comprises: firstly calcining the clay at a temperature of 830° C. for 2.2 hours, adding stearic acid monoglyceride after calcination, and mixing and stirring at a temperature of 70° C. for 70 minutes to obtain the modified clay; the weight ratio of the clay to stearic acid monoglyceride is 17:0.2.
[0051] This embodiment also provides a production process of a microcrystalline metal ceramic plate, comprising the following steps: weighing raw materials and mixing them to form a mixture, spray drying and granulating to obtain 90-mesh green body powder particles, drying and dry pressing, and drying at a temperature of 170° C. The moisture content of the green body after drying is 2.5%.
[0052] Comparative Example 2
[0053] The present comparative example provides a microcrystalline metal ceramic plate, which is composed of the following raw materials in parts by weight: 12 parts of kaolin, 15 parts of quartz sand, 12 parts of feldspar powder, 2 parts of silane coupling agent modified fiber, 13 parts of modified clay, 4.5 parts of polyvinyl alcohol, 0.5 parts of ammonium polymethacrylate, and 40 parts of water.
[0054] The preparation method of the modified fiber comprises: adding alumina fiber to deionized water and ultrasonically cleaning it for 1 hour, then immersing it in a sodium hydroxide aqueous solution with a temperature of 55° C. and a mass concentration of 3.5% to react for 35 minutes, washing it with water until it is neutral to obtain pretreated fiber, mixing the pretreated fiber, a silane coupling agent and ethanol, and reacting it at a temperature of 70° C. for 45 minutes, filtering it after the reaction is completed, and drying it to obtain the fiber;
[0055] Wherein, the length of the alumina fiber is 25 nm; the weight ratio of the alumina fiber, the silane coupling agent and ethanol is 7:2:55; and the silane coupling agent is KH550.
[0056] The preparation method of the modified clay comprises: firstly calcining the clay at a temperature of 830° C. for 2.2 hours, adding stearic acid monoglyceride after calcination, and mixing and stirring at a temperature of 70° C. for 70 minutes to obtain the modified clay; the weight ratio of the clay to stearic acid monoglyceride is 17:0.2.
[0057] This embodiment also provides a production process of a microcrystalline metal ceramic plate, comprising the following steps: weighing raw materials and mixing them to form a mixture, spray drying and granulating to obtain 90-mesh green body powder particles, drying and dry pressing, and drying at a temperature of 170° C. The moisture content of the green body after drying is 2.5%.
[0058] Comparative Example 3
[0059] The present comparative example provides a microcrystalline metal ceramic plate, which is composed of the following raw materials in parts by weight: 12 parts of kaolin, 15 parts of quartz sand, 12 parts of feldspar powder, 2 parts of silane coupling agent modified fiber, 13 parts of modified clay, 4.5 parts of polyvinyl alcohol, 0.5 parts of ammonium polymethacrylate, and 40 parts of water.
[0060] The preparation method of the modified fiber comprises: adding titanium dioxide fiber and aluminum oxide fiber to deionized water for ultrasonic cleaning for 1 hour to obtain pretreated mixed fiber, mixing the pretreated mixed fiber, silane coupling agent and ethanol, reacting at a temperature of 70° C. for 45 minutes, filtering after the reaction is completed, and drying to obtain the modified fiber;
[0061] Among them, the length of the titanium dioxide fiber is 110nm, the length of the aluminum oxide fiber is 25nm; the weight ratio of the titanium dioxide fiber, the aluminum oxide fiber, the silane coupling agent and ethanol is 9:7:2:55; the silane coupling agent is KH550.
[0062] The preparation method of the modified clay comprises: firstly calcining the clay at a temperature of 830° C. for 2.2 hours, adding stearic acid monoglyceride after calcination, and mixing and stirring at a temperature of 70° C. for 70 minutes to obtain the modified clay; the weight ratio of the clay to stearic acid monoglyceride is 17:0.2.
[0063] This embodiment also provides a production process of a microcrystalline metal ceramic plate, comprising the following steps: weighing raw materials and mixing them to form a mixture, spray drying and granulating to obtain 90-mesh green body powder particles, drying and dry pressing, and drying at a temperature of 170° C. The moisture content of the green body after drying is 2.5%.
[0064] Comparative Example 4
[0065] The present comparative example provides a microcrystalline metal ceramic plate, which is composed of the following raw materials in parts by weight: 12 parts of kaolin, 15 parts of quartz sand, 12 parts of feldspar powder, 2 parts of fiber, 13 parts of modified clay, 4.5 parts of polyvinyl alcohol, 0.5 parts of ammonium polymethacrylate, and 40 parts of water.
[0066] The fibers include titanium dioxide fibers and aluminum oxide fibers; wherein the length of the titanium dioxide fibers is 110 nm, and the length of the aluminum oxide fibers is 25 nm; and the weight ratio of the titanium dioxide fibers to the aluminum oxide fibers is 9:7.
[0067] The preparation method of the modified clay comprises: firstly calcining the clay at a temperature of 830° C. for 2.2 hours, adding stearic acid monoglyceride after calcination, and mixing and stirring at a temperature of 70° C. for 70 minutes to obtain the modified clay; the weight ratio of the clay to stearic acid monoglyceride is 17:0.2.
[0068] This embodiment also provides a production process of a microcrystalline metal ceramic plate, comprising the following steps: weighing raw materials and mixing them to form a mixture, spray drying and granulating to obtain 90-mesh green body powder particles, drying and dry pressing, and drying at a temperature of 170° C. The moisture content of the green body after drying is 2.5%.
[0069] Comparative Example 5
[0070] The present comparative example provides a microcrystalline metal ceramic plate, which is composed of the following raw materials in parts by weight: 12 parts of kaolin, 15 parts of quartz sand, 12 parts of feldspar powder, 2 parts of silane coupling agent modified fiber, 13 parts of modified clay, 4.5 parts of polyvinyl alcohol, 0.5 parts of ammonium polymethacrylate, and 40 parts of water.
[0071] The preparation method of the modified fiber comprises: adding titanium dioxide fiber and aluminum oxide fiber to deionized water for ultrasonic cleaning for 1 hour, then immersing in a sodium hydroxide aqueous solution with a temperature of 55° C. and a mass concentration of 3.5% to react for 35 minutes, washing with water until neutral to obtain a pretreated mixed fiber, mixing the pretreated mixed fiber, a silane coupling agent and ethanol, reacting at a temperature of 70° C. for 45 minutes, filtering after the reaction, and drying to obtain the modified fiber;
[0072] Among them, the length of the titanium dioxide fiber is 110nm, the length of the aluminum oxide fiber is 25nm; the weight ratio of the titanium dioxide fiber, the aluminum oxide fiber, the silane coupling agent and ethanol is 9:7:2:55; the silane coupling agent is KH550.
[0073] The preparation method of the modified clay comprises: adding clay to stearic acid monoglyceride, mixing and stirring for 70 minutes at a temperature of 70° C.; the weight ratio of the clay to stearic acid monoglyceride is 17:0.2.
[0074] This embodiment also provides a production process of a microcrystalline metal ceramic plate, comprising the following steps: weighing raw materials and mixing them to form a mixture, spray drying and granulating to obtain 90-mesh green body powder particles, drying and dry pressing, and drying at a temperature of 170° C. The moisture content of the green body after drying is 2.5%.
[0075] Comparative Example 6
[0076] The present comparative example provides a microcrystalline metal ceramic plate, which is composed of the following raw materials in parts by weight: 12 parts of kaolin, 15 parts of quartz sand, 12 parts of feldspar powder, 2 parts of silane coupling agent modified fiber, 13 parts of clay, 4.5 parts of polyvinyl alcohol, 0.5 parts of ammonium polymethacrylate, and 40 parts of water.
[0077] The preparation method of the modified fiber comprises: adding titanium dioxide fiber and aluminum oxide fiber to deionized water for ultrasonic cleaning for 1 hour, then immersing in a sodium hydroxide aqueous solution with a temperature of 55° C. and a mass concentration of 3.5% to react for 35 minutes, washing with water until neutral to obtain a pretreated mixed fiber, mixing the pretreated mixed fiber, a silane coupling agent and ethanol, reacting at a temperature of 70° C. for 45 minutes, filtering after the reaction, and drying to obtain the modified fiber;
[0078] Among them, the length of the titanium dioxide fiber is 110nm, the length of the aluminum oxide fiber is 25nm; the weight ratio of the titanium dioxide fiber, the aluminum oxide fiber, the silane coupling agent and ethanol is 9:7:2:55; the silane coupling agent is KH550.
[0079] This embodiment also provides a production process of a microcrystalline metal ceramic plate, comprising the following steps: weighing raw materials and mixing them to form a mixture, spray drying and granulating to obtain 90-mesh green body powder particles, drying and dry pressing, and drying at a temperature of 170° C. The moisture content of the green body after drying is 2.5%.
[0080] The microcrystalline metal ceramic plates prepared in Examples 1-4 and Comparative Examples 1-6 were tested, and the results are shown in Table 1 below:
[0081] Table 1
[0082]
[0083]
[0084] Finally, it should be noted that the above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents. All technical solutions and improvements that do not depart from the spirit and scope of the present invention should be included in the scope of the claims of the present invention.
Claims
1. A microcrystalline metal ceramic plate, characterized in that: The invention is composed of the following raw materials in parts by weight: 10-15 parts of kaolin, 10-20 parts of quartz sand, 10-15 parts of feldspar powder, 1-3 parts of silane coupling agent modified fiber, 12-14 parts of modified clay, 4-5 parts of polyvinyl alcohol, 0.4-0.6 parts of ammonium polymethylacrylate and 35-45 parts of water.
2. The microcrystalline metal ceramic plate according to claim 1, characterized in that: The preparation method of the modified fiber comprises: adding titanium dioxide fiber and aluminum oxide fiber to deionized water for ultrasonic cleaning for 1 hour, then immersing in a sodium hydroxide solution at a temperature of 50-60°C for reaction for 30-40 minutes, washing with water until neutral to obtain pretreated mixed fiber, mixing the pretreated mixed fiber, silane coupling agent and ethanol, reacting at a temperature of 65-75°C for 40-50 minutes, filtering after the reaction, and drying to obtain the modified fiber.
3. The microcrystalline metal ceramic plate according to claim 2, characterized in that: The length of the titanium dioxide fiber is 100-120 nm, and the length of the aluminum oxide fiber is 20-30 nm.
4. The microcrystalline metal ceramic plate according to claim 2, characterized in that: The sodium hydroxide solution is a sodium hydroxide aqueous solution with a mass concentration of 3-4%.
5. The microcrystalline metal ceramic plate according to claim 2, characterized in that: The weight ratio of the titanium dioxide fiber, the aluminum oxide fiber, the silane coupling agent and the ethanol is (8-10): (5-10): (1.5-2.5): (50-60).
6. The microcrystalline metal ceramic plate according to claim 2, characterized in that: The silane coupling agent includes at least one of KH550, KH560 and KH570.
7. The microcrystalline metal ceramic plate according to claim 2, characterized in that: The preparation method of the modified clay comprises: firstly calcining the clay at a temperature of 800-860° C. for 2-2.4 hours, adding stearic acid monoglyceride after calcination, and mixing and stirring at a temperature of 65-75° C. for 60-80 minutes to obtain the modified clay.
8. The microcrystalline metal ceramic plate according to claim 7, characterized in that: The weight ratio of the clay to stearic acid monoglyceride is (15-20):(0.1-0.3).
9. A production process for a microcrystalline metal ceramic plate as claimed in claims 1 to 8, characterized in that: The steps include: The raw materials are weighed and mixed to form a mixture, which is granulated by spray drying to obtain green body powder particles of 80-100 meshes, which are dry-pressed and formed after drying, and dried at a temperature of 160-180°C.
10. The production process of a microcrystalline metal ceramic plate according to claim 9, characterized in that: The moisture content of the green body after drying is 2-3%.
Citation Information
Patent Citations
Porous ceramic filter and preparation method thereof
CN101830729A
Brick and manufacturing process thereof
CN112960969A
Ultrathin ceramic rock plate and preparation method thereof
CN114436625A
Anti-crack ceramic tile and production process thereof
CN115259875A